Drip irrigation shapes the soil bacterial communities and enhances jujube yield by regulating the soil moisture content and nutrient levels - Zhaoyang Li; Wenhao Li; Jiulong Wang; Jinzhu Zhang; Zhenhua Wang (Agricultural Water Management, 2023)
In the agricultural zones of the arid Xinjiang region of China, reducing irrigation is mandatory. However, irrigation affects the composition and diversity of the soil bacterial community which is vital to crop yield. To the best of our knowledge, very little research has been conducted on the relationships among the soil bacterial community, irrigation method, and yield as well as their underlying in jujube agroecosystems. Here, we investigated the soil physicochemistry and bacterial communities in jujube fields subjected to drip irrigation (DI) and traditional flood irrigation (FI), and their associations with yield at the flowering and fruit set (FFS) and end-of-growth (EG) stages. Under DI, the jujube yield was 8712.00 ± 24.54 kg/hm2, which was 7.64% higher than that obtained under FI (8094.33 ± 43.67 kg/hm2). DI increased the relative soil bacteria community diversity by decreasing the moisture content and increasing the nutrient levels in the soil. DI also transformed the soil bacterial community so that Bacteroidota predominated at the FFS stage and the probiotics Chloroflexi and Firmicutes predominated at the EG stage. A co-occurrence network analysis showed that DI created stable complex Soil bacteria communities in jujube fields, Though Dependentiae and Deferriberota had low relative abundance, they were nonetheless key nodes in the soil bacterial community network. A neutral community model (NCM) revealed that stochastic processes drove the soil bacterial community assembly whereas DI promoted deterministic processes by regulating the soil moisture content and nutrient levels. Partial least squares path modeling (PLS-PM) disclosed that DI affected the soil bacterial community structure by decreasing the moisture content (−0.342 **) and increasing the nutrient levels (0.557 **) in the soil. The PLS-PM also demonstrated that the observed change in the soil bacterial community structure was the main reason for the increase in jujube yield (1.098 **). The present work provides insights into the mechanisms underlying the correlations between the soil bacterial community and crop yield in response to changes in the irrigation method.